The acceptability of primary care or community‐based behavioural interventions for persistent physical symptoms: Qualitative systematic review. Issue 4 (2nd April 2021) - Scope, Alison; Leaviss, Joanna; Booth, Andrew; Sutton, Anthea; Parry, Glenys; Buszewicz, Marta; Moss‐Morris, Rona
Abstract : Purpose: Persistent physical symptoms (PPS) are often associated with profound physical disability and psychological distress. Interventions for PPS that promote behavioural change aim to reduce levels of symptoms and improve overall functioning in patients. The evidence for these interventions is mixed, with effective relationships between patients and health practitioners (HPs) reported as the key to the success of primary care interventions. The objectives of this systematic review were to synthesize the qualitative evidence and to evaluate the acceptability of behavioural interventions for PPS in primary care, from the perspective of both patients and HPs. Methods: A comprehensive literature search was conducted in seven major electronic bibliographic databases, to February 2019. The aim was to identify a broad range of literature including, qualitative research, mixed methods research, and qualitative data embedded in trial reports or process evaluations. Fifty‐eight full papers were screened against the inclusion criteria. Nine studies were included and quality‐assessed. A qualitative evidence synthesis was conducted using thematic synthesis. Results: Some patients and HPs reported positive gains from taking part in or delivering interventions, with appropriate support and explanation of their symptoms important for patients. Barriers appeared to be underpinned by the relationship between the patients and HPs, and by beliefs and attitudes held by both parties. Conclusions: Patients should be provided with adequate information to make an informed decision about whether an intervention is appropriate for them, and interventions should not end suddenly or without adequate follow‐up. HPs should receive training and supervision to address their lack of confidence, and improve their knowledge of PPS.